Dzialania energooszczedne w rolnictwie (Energy saving measures in agriculture) - Golaszewski, J (2014)
The reduction of energy inputs in agricultural production is a process of practical implementation of a set of energy saving (ES) measures associated with a given type of production, farm infrastructure and managerial or organizational activities. In six national reports from Finland, Germany, Greece, the Netherlands, Poland and Portugal for 13 subsectors of agriculture, 481 ES measures in total were identified and classified into seven categories: 1) type of energy input: indirect, direct; 2) type of ES measure: operational level, systems level, process monitoring, farm management, market orientation, capital goods; 3) importance: from 1-low to 5-high; 4) R&D: yes, no; 5) potential of the measure: achievable at present or not immediately ready for implementation; 6) indication of an investment cost: from €1000 to over €1000000; 7) estimated payback time: from 1 to over 5 years.  The general conclusions from the analysis are as follows.ES measures refer to the reduction of main energy inputs in agricultural production, including fertilizers and pesticides; fuels for powering tractors and other machinery; fuel use for heating, cooling, and ventilation in farm buildings and facilities; electricity use for pumping, lighting; and energy embodied in buildings and equipment.  In general, the listed ES measures can reduce both direct and indirect energy inputs and the overwhelming majority of the ES measures (443 out of 481) were assessed in the range from 3 (moderate) to 5 (high) in terms of their importance for energy saving. The implementation of part of the ES measures in agricultural practice is achievable at presente Agriculture and Energy Efficiency 4 (464 out of 481) but will require some advanced research (389 out of 481). In the highly industrialized production of pigs and broilers, there are many ES measures which may be implemented with technologies which are presently on the market such as improved heat insulation, more efficient ventilation, lighting and cooling systems, as well advanced control of the interior climate.  R&D will be especially important for progress in attaining energy efficiency in agriculture when applied to systems involved in the production process, operational activity and capital goods/farm infrastructure engaged in production.  The estimated categories of investment costs related to implementation of ES measures vary greatly between subsectors. 1/3 of the total number of the measures can be implemented at a cost under €1000, and 1/3 incur costs in the range from €1000 to €25000. The highest investment costs would be associated with saving energy and improving energy efficiency in greenhouses and livestock production. They are associated with improved heat insulation, more efficient ventilation, lighting and cooling systems, as well advanced control of the interior climate.  In crop production, energy saving will be considerably affected by the ES measures associated with reduction of diesel fuel use by optimizing the parameters for tractor and machinery use in field operations, reduction of energy use for drying and in produce stores. On the other hand, reduction of indirect energy input is associated with implementation of ES measures related to advanced high-yield and disease-resistant cultivars, application of alternative sources of nutrients and plant protection (organic and green fertilizers, bioactive microorganisms), advanced monitoring of the production process and use of production means in accordance with the soil fertility and plant nutrient uptake (Precision Arable Agriculture with Variable Rate application). The importance of ES activities may be country-specific, e.g. in the southern EU countries more importance will be attributed to the ES measures associated with irrigation of cultivated crops while in the central and north-eastern countries – to the ES measures associated with energy effective drying techniques for the harvested crop..  In perennial crop production, the majority of ES measures are connected with fertilization, plant protection and field operations.  In greenhouse production, potential reduction of direct energy inputs is associated with the control of greenhouse atmosphere by energy efficient systems of heating, cooling and ventilation as well optimization of production processes. There are also importante measures connected with new solutions for energy recovery and the use of other,alternative sources of energy.  The structure of ES measures in livestock production depends on the country. In Portugal,Poland and Finland many ES measures are associated with the production of animal feed and the promotion of animal welfare. However in the Netherlands and Germany most of the reported ES measures are related to electricity use and to the buildings and associated infrastructure for livestock production. Energy use in livestock production may be reduced by increased efficiency of production inputs which require energy consumption, e.g. water use and cleaning, heat insulation, ventilation, reduction of amount of ammonia in buildings, heat recovery, energy use optimization for a given production system.